Quantitative proteomic analysis to reveal expression differences for butanol production from glycerol and glucose by Clostridium sp. strain CT7 - Yujia Jiang; Ruofan Wu; Jiasheng Lu; Weiliang Dong; Jie Zhou; Wenming Zhang; Fengxue Xin; Min Jiang (Microbial Cell Factories, 2021)
Abstract Clostridium sp. strain CT7 is a new emerging microbial cell factory with high butanol production ratio owing to its non-traditional butanol fermentation mode with uncoupled acetone and 1,3-propanediol formation. Significant changes of metabolic products profile were shown in glycerol- and glucose-fed strain CT7, especially higher butanol and lower volatile fatty acids (VFAs) production occurred from glycerol-fed one. However, the mechanism of this interesting phenomenon was still unclear. To better elaborate the bacterial response towards glycerol and glucose, the quantitative proteomic analysis through iTRAQ strategy was performed to reveal the regulated proteomic expression levels under different substrates. Proteomics data showed that proteomic expression levels related with carbon metabolism and solvent generation under glycerol media were highly increased. In addition, the up-regulation of hydrogenases, ferredoxins and electron-transferring proteins may attribute to the internal redox balance, while the earlier triggered sporulation response in glycerol-fed media may be associated with the higher butanol production. This study will pave the way for metabolic engineering of other industrial microorganisms to obtain efficient butanol production from glycerol.